Dlaczego Owidiusz został wygnany? Literatura jako narzędzie rozwiązywania zagadek z przeszłości. - Gawarecka, Anna (Slavia Occidentalis, 2011)
Two writers, Jacek Bocheński and Josef Škvorecký, in different times and in a different cultural situation, independently, embarked on a task to solve one of the mysteries from the history of literature, namely, the reasons for Ovid’s banishment. In the novels Nazo poeta and Nevysvětlitelný příběh aneb vyprávění Questa Firma Sicula both writers seek the answer to the question about the reasons for the exile of the author of Metamorphoses. They are trying to reveal the autobiographical information coded in the plots of Ovid’s poems and in the metaphors of lyrical utterances, subordinated to the rules of the ancient poetics. They both know that in the situation when the texts are the only source of information, they must be the primary way to reach the truth. Although the exposed intertextuality emphasizes pozareferencjalny dimension of the story, in practice it turns out to be, what both authors claim in their novels, the only instrument for perceiving reality.